Aortic Root Dilatation in Children and Adolescents At Al-Hawary General Hospital, & National Benghazi Cardiac Center -Libya - Rasmia H. Feituri; Hanan El Megasbi; Mariam M. El maadani; Amal Khazm (مجلة المختار للعلوم, 2021)
Isolated dilatation of the aortic root and/or ascending aorta is a rare but well-known cardiovascular manifestation, can be caused by a variety of congenital or acquired conditions; that lead to the weakening of the aortic wall. The study aimed to detect the cause and the rate of the aortic root dilatation in children and adolescents, and to assess the effect of the Beta-adrenergic blockers in preventing further dilatation in the aortic root. A case series study was perform with five years of follow-up at Al-Hawary General Hospital, National Benghazi Cardiac Center. A total of 91 patients were seen with ascending aortic dilatation and/or root dilatation during the period from 6/2016 - 6/2021 included in the study diagnosed by clinical examination, chest x-ray, and echocardiogram. The diagnosis in 34/91(37%) was Tetralogy of fallout (TOF) and truncus arteriosus, 57/91 (63%) was dilated aortic root, 25/57 (44%) bicuspid aortic valve (BAV), 22/57 (38.5%) Marfan syndrome, 4/57(7%) Noonan syndrome, 2/57(3.5%) Turner syndrome, 3/57(5%) Ehlers-Danlos syndrome, 1/57(2%) idiopathic. Follow-up results of three months – five years: 57/91 patients with aortic root dilatation were followed up, none of the Marfan syndrome and Ehlers-Danlos syndrome patients who received beta-blockers had shown progression in the dilatation of the aortic root, and all patients who had bicuspid aortic valve did not show any progression in the dilatation without using medication. Conclusions: Dilated aortic root is a common finding in Marfan syndrome, bicuspid aortic root, and Ehlers-Danlos syndrome, and its progress could be decreased by using beta-adrenergic blockers in rapidly progressing dilation.